Alternative Analysis of Financing Receipts in the DKI Jakarta Provincial Government using the Regulatory Impact Analysis Method - Rusmawati, Triana; Umanto, Umanto (Program Pascasarjana Universitas Negeri Makassar, 2025)
Regulatory Impact Analysis (RIA) is a method to ensure that policies made are effective and efficient and can minimize negative impacts on society. In this regard, this study aims to analyze alternative financing receipts in the DKI Jakarta Provincial Government using the RIA method. This study uses a qualitative data collection method with interviews and document studies. Interviews were conducted with policy makers at the Regional Financial Management Agency as the Regional Work Unit that has the authority to make decisions regarding alternative financing receipts. The results of the study indicate that based on the Regulatory Impact Analysis method, the alternative financing receipt that should be used by the DKI Jakarta Provincial Government is the Disbursement of Regional Reserve Funds. Other alternatives such as the use of the remaining budget from the previous year, the proceeds from the sale of separated regional assets, receipt of regional loans, and re-receipt of regional loans have several shortcomings compared to the alternative Disbursement of Regional Reserve Funds.